Implementation of the SMart-Punakawan Covid-19 (Sebelas Maret-Pendampingan UNtuk mAsyarakat dan KeluargA melaWAN Covid-19) in Surakarta - Eti Poncorini Pamungkasari; Bulan Kakanita Hermasari; Sri Anggarini Parwatiningsih; Sri Mulyani; Hartono Hartono; Lely Tri Pangesti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
The Covid 19 pandemic cannot be predicted when it will end. In June 2021, there has been very significant increase in new cases. The government has tried to control transmission by launching the 5M propaganda, consists of wearing masks, maintaining distance, washing hands with soap, avoiding crowds and reducing mobility. However, there are still problems existing related to community compliance in preventing the transmission of Covid 19, for example the use of masks and avoiding crowds. The aim of this project is develop and implement health education media related to Five M and Covid-19 vaccination.This project begins with development education media considering cultural wisdom, in order to easily accepted by the community. The term SMart-Punakawan Covid-19 (Sebelas Maret-Pendampingan UNtuk mAsyarakat dan KeluargA melaWAN Covid-19) was chosen to named this media. Punakawan is a puppet character, the